The historiography of religion as knowledge of the historical nature of religion - Borys Lobovyk (Українське Pелігієзнавство, 1999)
The historiography of religion is the branch of religious studies, which is on the verge of the history and philosophy of religion. With regard to these latter, it has common and special features. If history studies the origin and development of religion in its states and forms, if the philosophy of religion is intended to give a theoretical understanding of the essence and meaning of religion as such, then the historiosophy of religion is a doctrine of the historical nature of the phenomenon of religiosity taken in integrity with its essence. In this sense, the historiosophy of religion can be called the phenomenology of religious studies.